Pigs and Cows: Peace walls and sectarianism in Northern Ireland - Desrochers, Éric (Glendon Journal of International Studies, 2017)
Abstract: Northern Ireland has a long history of sectarian strife between its Catholic and Protestant communities, culminating with the Troubles, the decades long conflict between British state forces and unionist and nationalist paramilitary groups which raged from the 1960s to 1990s. Despite the end of open conflict, Northern Ireland has remained bitterly divided along sectarian lines. This remains true today, almost 20 years since the cessation of hostilities. This paper looks at sectarianism in Belfast, notably through the "peace walls" dividing Protestant and Catholic neighbourhoods, and how they function as de facto borders as well as other manifestations of sectarianism, such as social interactions and electoral behaviour. Résumé : L’Irlande du Nord a une longue histoire de lutte sectaire entre les communautés catholiques et protestantes, culminant dans les Troubles, le conflit qui a duré plusieurs décennies entre les forces de l’état et les groupes unionistes et nationalistes paramilitaires. Malgré la fin du conflit ouvert dans les 1990s, l’Irlande du Nord reste profondément divisée selon des lignes sectaires. Ceci est vrai aujourd’hui, presque vingt ans après la fin des hostilités. Cet article examine le sectarisme à Belfast, notamment en analysant les « murs de paix » divisant les quartiers protestants et catholiques, et comment ils fonctionnent de facto comme des frontières, ainsi que d’autres manifestations du sectarisme, comme les interactions sociales et le comportement électoral.